Superradiant phase transition with graphene embedded in one dimensional optical cavity - Li, Benliang (2019)
We theoretically investigate the cavity QED of graphene embedded in an optical cavity under perpendicular magnetic field. We consider the coupling of cyclotron transition and a multimode cavity described by a multimode Dicke model. This model exhibits a superradiant quantum phase transition, which we describe exactly in an effective Hamiltonian approach. The complete excitation spectrum in both the normal phase and superradiant phase regimes is given. In contrast to the single mode case, multimode coupling of cavity photon and cyclotron transition can greatly reduce the critical vacuum Rabi frequency required for quantum phase transition, and dramatically enhance the superradiant emission by fast modulating the Hamiltonian. Our work paves a way to experimental explorations of quantum phase transitions in solid state systems.